Complete separation of the quaternary mixture of nadolol stereoisomers using preparative and simulated moving bed chromatography - Arafah, Rami (2021)
The separation and purification of high added value products by liquid chromatography is a very popular technique. The development of more stable and efficient stationary phases, together with the design of innovative and more flexible separation processes, enhanced the use of chromatographic processes, particularly at preparative and industrial scales through fixedbed and simulated moving bed (SMB) technologies. Fixed-bed and SMB techniques are more and more used in the separation of a wide range of products for the pharmaceutical, fine chemistry, biotechnology and food industries. In this context, one of the actual main challenges concerns the design and optimization of these chromatographic processes for challenging multicomponent separations. This includes the development of new and innovative chromatographic processes, combining different design strategies and modes of operation, with different types of stationary and mobile phases.